Service user Outcomes of staff training in positive behaviour support using person‐focused training - Grey, Ian I. (2006)
Background Effectively supporting individuals with intellectual disabilities who display challenging behaviours continues to be a priority for service providers. Person‐focused training (PFT) is a model of service delivery which provides staff with skills in functional assessment and intervention development. Existing longitudinal data from a study of 138 cases suggest that implementation of staff‐developed behaviour support plans through PFT is effective in reducing challenging behaviour in approximately 77% of cases [McClean et al.Journal of Intellectual Disability Research (2005) vol. 49, pp. 340–353]. However, no control group was used in this study. Method The current study involves the use of a control group of individuals with challenging behaviours matched against those selected for PFT over a 6‐month period. Groups were matched on type of challenging behaviour, duration of challenging behaviour, gender and level of disability. Information on the frequency, management difficulty and severity of challenging behaviour was collected pre‐ and post‐training using the Checklist of Challenging Behaviours (CCB) for both groups. Observational data were collected for the target group alone. Rates of psychotropic medication were tracked across the training period. Results Significant reductions in the frequency, management difficulty and severity of challenging behaviour were found for service users in the target group but not in the control group after 6 months. No significant changes were found in the use of psychotropic medication for either group over the 6‐month period. Conclusion Overall results suggest that PFT is an effective model for providing support to individuals with challenging behaviours.